Ultrastructural analysis of the low level laser therapy effects on the lesioned anterior tibial muscle in the Gerbil - Iyomasa, Daniela Mizusaki [UNESP]; Garavelo, Ivania [UNESP]; Iyomasa, Mamie Mizusaki; Watanabe, Ii-sei; Mardegan Issa, Joao Paulo (Pergamon-Elsevier B.V. Ltd, 2009)
Low level laser therapy (LLLT) is known for its positive results but studies on the biological and biomodulator characteristics of the effects produced in the skeletal muscle are Still lacking. In this Study the effects of two laser dosages, 5 or 10 J/cm(2), on the lesioned tibial muscle were compared. Gerbils previously lesioned by 100 g load impact were divided into three groups: GI (n = 5) controls, lesion non-irradiated; GII (n = 5), lesion irradiated with 5 J/Cm(2) and GIII (n = 5), lesion irradiated with 10 J/cm(2), and treated for 7 consecutive days with a laser He-Ne (lambda = 633 rim). After intracardiac perfusion, the muscles were dissected and reduced to small fragments, post-fixed in 1% osmium tetroxide, dehydrated in increasing alcohol concentrations, treated with propylene oxide and embedded in Spurr resin at 60 degrees C. Ultrafine Cuts examined on a transmission electron microscope (Jeol 1010) revealed in the control GI group a large number of altered Muscle fibers with degenerating mitochondria, intercellular substance containing degenerating cell fragments and budding blood capillaries with Underdeveloped endothelial cells. However, groups GII and GIII showed muscle fibers with few altered myofibrils, regularly contoured mitochondria, ample intermembrane spaces and dilated mitochondrial crests. The clean intercellular Substance showed numerous collagen fibers and capillaries with multiple abluminal processes, intraluminal protrusions and several pinocytic vesicles in endothelial cells. it was concluded that laser dosages of 5 or 10 J/cm(2) delivered by laser He-Ne (lambda = 633 rim) during 7 consecutive days increase mitochondrial activity in muscular fibers, activate fibroblasts and macrophages and stimulate angiogenesis, thus suggesting effectivity of laser therapy tinder these experimental conditions. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Tissue repair; Skeletal muscle; Capillary remodeling; Muscular lesion; Low level laser therapy; Ultrastructure